Tinjauan Yuridis Tentang Perlindungan Hukum Bagi Korban Kejahatan Siber Di Indonesia - Fitra, Muhammad; Kamaruddin; Dagani, Gamlan (Sekolah Tinggi Ilmu Hukum Sumpah Pemuda, 2025)
The development of digital technology in Indonesia has brought significant changes in social and economic interaction patterns, but it has also led to an increase in cybercrime, which has a serious impact on victims. This study aims to analyse the national legal framework related to the protection of victims of cybercrime and assess the effectiveness of access to justice and electronic evidence in the Indonesian legal system. The method used is normative legal research with a statutory and conceptual approach, as well as analysis through grammatical, systematic, and teleological interpretation of Law Number 11 of 2008 concerning Electronic Information and Transactions (ITE Law), Law No. 27 of 2022 concerning Personal Data Protection, and Law No. 31 of 2014 concerning Witness and Victim Protection. The results of the study show that although victim protection has been regulated normatively, its implementation is still not optimal due to weak institutional coordination, limited digital forensic resources, and a lack of legal standards for electronic evidence processes. It is important to strengthen regulations, improve law enforcement capacity, and apply digital restorative justice to ensure the full restoration of victims' rights.